Multimedia educativa de apoyo en el proceso para la enseñanza-aprendizaje de la asignatura de ciencias sociales del cuarto año de educación general básica para los (as) niños (as) de la unidad educativa, “Soberanía Nacional” del cantón Paquisha, provincia de Zamora Chinchipe, período lectivo 2013-2014 - Quinche Benítez, Favián Honorio (2015)
The present research have like an objective to make an educational multimedia to reinforce the knowledge in the teaching and learning process to the Social Studies subject applied to Fourth year of primary "Soberanía Nacional" School from Paquisha-Zamora Chinchipe Province, 2013-2014 school year. In the development of this research was used the following methods: inductive and deductive for the bibliographic revision, according to the teaching and learning variables and multimedia; another method is analytic, the same that served to do the respective analysis in relation to the variables and the elaboration of the conclusions and recommendations of the matter researched; it is very important to write down that the statistic method was also used in the tabulation of results with the presentation of graphs and charts where the information about frequencies and percentages are presented. The technique applied was the survey in which, by means of a quiz the students of Fourth year of primary School were asked to answer. The results got are very interesting, because the new didactic resource is giving solution to some educational problems related to Social Studies subject. For the development of this multimedia used the waterfall method, the same that allowed to design an interface of easy management for the user, as well as adaptability and operation tests in some educational institutions to fourth year level, taking into account the best and effective operation. According to the applied survey to eleven students of Fourth year of primary school was determined that, a 91% of students like the methodology used by the teacher at the moment that he teaches his classes about Social Studies.